Stomatal and Non-Stomatal Leaf Traits for Enhanced Water Use Efficiency in Rice - Yvonne Fernando; Mark Adams; Markus Kuhlmann; Vito Butardo Jr (Biology, 2025)
Globally, rice cultivation consumes large amounts of fresh water, and urgent improvements in water use efficiency (WUE) are needed to ensure sustainable production, given increasing water scarcity. While stomatal traits have been a primary focus for enhancing WUE, complex interactions between stomatal and non-stomatal leaf traits remain poorly understood. In this review, we present an analysis of stomatal and non-stomatal leaf traits influencing WUE in rice. The data suggests that optimising stomatal density and size will be insufficient to maximise WUE because non-stomatal traits such as mesophyll conductance, leaf anatomy, and biochemical composition significantly modulate the relationship between stomatal conductance and the photosynthetic rate. Integrating recent advances in high-throughput phenotyping, multi-omics technologies, and crop modelling, we suggest that combinations of seemingly contradictory traits can enhance WUE without compromising yield potential. We propose a multi-trait breeding framework that leverages both stomatal and non-stomatal adaptations to develop rice varieties with superior WUE and climate resilience. This integrated approach provides a roadmap for accelerating the development of water-efficient rice cultivars, with broad implications for improving WUE in other crops.